Adubação de gramíneas forrageiras com dejeto líquido de suíno - Silva, Marinho Rocho da (2016)
Pig farming is an important economic activity, and there is no need for large areas for the development of its production system. High density of animals implies a greater accumulation of organic residues that are composed of faeces, urine, leftover rations, leftover water from drinking fountains and water from the hygienization of sheds. In view of the problem of the destination of these swine residues and the expressiveness of grazing animals, the objective was to use the liquid swine waste (DLS) in the fertilization of Brachiaria brizantha and Cynodon dactylon. Two experiments were carried out: one in a greenhouse and the other in the field. In the greenhouse experiment, the design was in randomized blocks with fifteen treatments and four replications. The treatments were arranged in a 3x5 factorial scheme, being three cultivars of B. brizantha (Marandu, Xaraés and Piatã) and five doses of DLS. Doses were set to 0; 25; 50; 75 and 100 mg N dm-3 which according to the content of Nitrogen (N) contained in DLs corresponded to 0,0; 3,5; 7,0; 10,5 and 14 g dm-3 vessel. The application of DLS independent of the cultivar provided an increase in dry mass, plant height, number of tillers, number of leaves and crude protein (CP) content, besides linearly reducing neutral detergent fiber (NDF) and Acid detergent fiber (FDA). In the field experiment the tifton 85 grass was used. The design was in a randomized block with 5 treatments and 4 replicates. Treatments consisted of the following doses: 0,0; 70; 140 and 210 m3 ha-1 of DLS applied divided into seven cuts and a mineral dose of 200 kg of N ha-1 in two production cycles. Greater plant height, dry mass production, higher CP content, higher PIDIN content and lower NDF content were observed in tifton 85 grass in mineral fertilization. In the variables FDA and PIDA there was no significant difference (P <0.05) between the DLS dose and the mineral fertilization. The results evidenced the need for studies with higher doses of DLS for tifton grass 85.